(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Traditional herbal teas have long been celebrated for their therapeutic properties and cultural significance across various civilizations. In recent years, the integration of these herbal teas into modern nutritional therapy has garnered significant attention due to their potential pharmacological benefits. This paper explores the bioactive compounds present in popular herbal teas, including chamomile, peppermint, green tea, and rooibos, and their roles in enhancing health and wellness. These teas are rich in polyphenols, flavonoids, and essential oils, which exhibit antioxidant, anti-inflammatory, and antimicrobial properties. The review delves into the mechanisms by which these compounds contribute to the prevention and management of chronic diseases such as cardiovascular disorders, diabetes, and gastrointestinal issues. Additionally, the paper highlights emerging research on the role of herbal teas in modulating immune responses, promoting mental well-being, and supporting weight management. While traditional herbal teas offer a natural and holistic approach to health, the paper also addresses the challenges related to standardization, dosage, and potential interactions with conventional medications. By synthesizing current evidence from both historical texts and contemporary scientific studies, this review aims to provide a comprehensive understanding of the pharmacological benefits of herbal teas and their applicability in modern nutritional therapy. The findings underscore the importance of integrating traditional knowledge with modern research to optimize the use of herbal teas in promoting health and preventing disease.